Device‐to‐Materials Pathway for Electron Traps Detection in Amorphous GeSe‐Based Selectors. (7th February 2023) - Slassi, Amine; Medondjio, Linda‐Sheila; Padovani, Andrea; Tavanti, Francesco; He, Xu; Clima, Sergiu; Garbin, Daniele; Kaczer, Ben; Larcher, Luca; Ordejón, Pablo; Calzolari, Arrigo
Abstract: The choice of the ideal material employed in selector devices is a tough task both from the theoretical and experimental side, especially due to the lack of a synergistic approach between techniques able to correlate specific material properties with device characteristics. Using a material‐to‐device multiscale technique, a reliable protocol for an efficient characterization of the active traps in amorphous GeSe chalcogenide is proposed. The resulting trap maps trace back the specific features of materials responsible for the measured findings, and connect them to an atomistic description of the sample. The metrological approach can be straightforwardly extended to other materials and devices, which is very beneficial for an efficient material‐device codesign and the optimization of novel technologies. Abstract : A metrological materials‐to‐device computational approach that extracts defects characteristics from the experimental device electrical data and connects them to the microscopic properties of the material is proposed. This protocol is applied to amorphous GeSe‐based ovonic threshold switching selectors. This method unveils the role of electrical traps in amorphous materials and connects them to the device electrical characteristics.